Prognostic and Predictive Values of E-Cadherin for Patients of Ovarian Clear Cell Adenocarcinoma. Issue 9 (1st November 2010) - Ho, Chih-Ming; Cheng, Wen-Fang; Lin, Ming-Chieh; Chen, Tze-Chien; Huang, Shih-Hung; Liu, Fu-Shing; Chien, Chan-Chao Chang; Yu, Mu-Hsien; Wang, Tao-Yeuan; Hsieh, Chang-Yao
Abstract : Objectives: The purpose of the study was to analyze negative versus positive immunoexpression of epithelial cadherin (E-cadherin) and p53 in patients with primary advanced ovarian clear cell adenocarcinoma (OCCA) and its significance in relation to clinical features, progression-free survival and overall survival (OS). Methods and Materials: Protein expression of E-cadherin and p53 was immunohistochemically evaluated in 61 OCCA patients with stages IIC to IV. The clinical factors studied included stage, age, CA-125, residual tumors, and chemotherapy regimens. Results: Positive p53 immunoexpression was 44.8% (26/58) of OCCAs; in contrast, E-cadherin immunoexpression was observed in 75.9% (44/58) of OCCAs. The expected 5-year OS rate of OCCA treated with paclitaxel-based chemotherapy was significantly better than non-paclitaxel-based chemotherapy (40% vs 0%, P = 0.001). The expected 5-year OS rate of OCCA patients with positive E-cadherin immunoexpression (>10%) was also significantly better than patients with negative E-cadherin immunoexpression (≤10%) (35% vs 0%, P = 0.02). The expected 5-year OS rate of those receiving paclitaxel-platinum chemotherapy was not significantly different from platinum-based chemotherapy for those with negative E-cadherin immunoexpression ( P = 0.11). The expected 5-year OS rate of those receiving paclitaxel-based chemotherapy was better than non-paclitaxel-based chemotherapy for those with positive E-cadherin immunoexpression (43% vs 0%, P = 0.01). Paclitaxel-based chemotherapy and positive E-cadherin immunoexpression were 2 independent prognostic factors in OS of patients with OCCA ( P = 0.01 and 0.04, respectively). Conclusions: E-cadherin is a useful prognostic marker for OCCA patients, and paclitaxel-based chemotherapy can improve survival among patients with positive E-cadherin immunoreactivity.